2000
DOI: 10.1046/j.1365-2168.2000.01471.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of laparoscopic versus open fundoplication: blind evaluation of recovery and discharge period

Abstract: Laparoscopic fundoplication was associated with a longer operating time, better respiratory function, less need for analgesics and a shorter hospital stay, while no reduction in the duration of postoperative sick leave was found compared with open surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
2
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(70 citation statements)
references
References 14 publications
3
62
2
3
Order By: Relevance
“…The mean preoperative quality of life score was 32.34 6 4.28 (22-38); postoperatively, the average value of this score decreased to 4.76 6 0.92 (3)(4)(5)(6). In the postoperative period, GERD-HRQL scores were significantly decreased compared to the preoperative period (P ¼ 0.001).…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The mean preoperative quality of life score was 32.34 6 4.28 (22-38); postoperatively, the average value of this score decreased to 4.76 6 0.92 (3)(4)(5)(6). In the postoperative period, GERD-HRQL scores were significantly decreased compared to the preoperative period (P ¼ 0.001).…”
Section: Resultsmentioning
confidence: 77%
“…With the development of laparoscopic antireflux surgery, reductions have been achieved in morbidity, mortality and even in the rate of recurrence of surgical treatment. 6 Moreover, although successful results of laparoscopic antireflux surgery have been reported, the limited number of studies comparing surgical and medical treatment has prevented resolution of this debate. Given the prognosis of the disease, the incidence of complications is also increasing with the severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that laparoscopic fundoplication has multiple benefits over the traditional open approach, including improved cosmesis, reduced morbidity, decreased hospital stay, decreased respiratory complications, and faster recovery (1)(2)(3). The long-term outcomes of laparoscopic fundoplication are comparable to open surgery in subjective symptoms.…”
Section: Introductionmentioning
confidence: 67%
“…Laparoskopik ameliyatların popüler olmasından sonra cerrahi endikasyonlar tekrar gözden geçirilmiş ve tedavi algoritmasındaki yeri yeniden önem kazanmıştır. Laparoskopik yöntemlerin gelişmesi ve yaygınlaşması ile cerrahi tedavinin morbidite, mortalite ve nüks oranlarında düşme görülmüştür [3]. Laparoskopik antireflü cerrahi yapılan hastaların uzun dönem takibinde, hastaların çoğun-da mükemmel sonuçların elde edildiği görülmüştür [4,5].…”
Section: Introductionunclassified